Sin & chocolate eaudiobook - Breene, K.F (Demigods of San Francisco, 2024)
"A broody, broken god and the dark secrets that could destroy us both. Kieran is here for revenge. He's here to kill the most powerful man in Magical San Francisco— his father. He'll destroy anything in his way. And I've managed to catch his eye. I live in the shadows for a reason, split between the worlds of the magical and the mundane. I'm a punching bag for both societies, but with the magic of Hades, it's the only way to stay alive. To stay free. If the powers that be knew what I was, they'd slap me in a cage and make me their weapon. I have to stay away from him...except the very look of him promises deliciously wicked sin. He's a man you want to taste. To savor, like decadent chocolate. He's also incredibly powerful, and broken. Dangerous. I can't let him use my magic. It would destroy the life I've struggled so hard to build. I certainly can't fall for the villain, no matter how good it would feel. If only it was easy to walk away. Performed by Yenni Ann, Yasmin Tuazon, Alex Hill-Knight, Lena Lee, Robb Moreira, Rayner Gabriel, Danny Gavigan, Gabriel Michael, Matthew Pauli, Andrew James Spooner, Bradley Foster Smith, Bill Gillett, Chris Stinson, Christopher Walker, Christopher Williams, Colleen Delany, David Cui Cui, Dawn Ursula, Drew Kopas, Eric Messner, Jeri J. Marshall, Jon Vertullo, Jonathan David Bullock, Julienne Irons, Karen Novack, Kay Eluvian, Ken Jackson, Lise Bruneau, Lydia Kraniotis, Marni Penning, Michael John Casey, Nanette Savard, Natalie Van Sistine, Nora Achrati, Rose Elizabeth Supan, Ryan Dalusung, Scott McCormick, Shanta Parasuraman, Stephanie Nemeth-Parker, Steve Wannall, Terence Aselford, Triya Leong, and Wayne LeGette."